Coordinated corrective control for model matching of asynchronous sequential machines - Yang, Jung Min; Lee, Dong Eun; Park, Seong Jin (International Journal of Systems Science, 2020)
This paper proposes coordinated corrective control of input/state asynchronous sequential machines (ASMs). The states of the considered ASM are physically or logically separated to which complete observation by a single controller is impossible. A number of local dynamic controllers that have access to local states cooperate to match the stable-state behaviour of the closed-loop system to that of a reference model. We investigate reachability description of ASMs in the configuration of coordinated control and present the existence condition and design procedure for local controllers that solve the model matching problem. An illustrative example is provided to validate the proposed coordinated corrective control scheme.
Keywords: Asynchronous sequential machines; Co-ordinated control; Corrective control; Existence conditions; Local controllers; Model matching problems; Reference modeling; Single controllers; Asynchronous sequential machines (ASMs); coordinated control; dynamic corrective control; model matching